Secondary battery and electric device

By adding lithium borate to the electrolyte of the dry battery, the problems of low first discharge capacity and fast cycle capacity decay are solved, and the effect of improving the first effect of the battery and extending the cycle life is achieved.

CN119601664AInactive Publication Date: 2025-03-11NIO TECH ANHUI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510144594.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The first discharge capacity of the dry process system battery is low and will cause faster capacity attenuation at the beginning of the cycle, mainly due to the reduction of the binder polytetrafluoroethylene (PTFE).

Method used

By adding lithium borate as an additive to the electrolyte solution, PTFE is preferentially reduced during the first charge and discharge process using its high reduction potential to form a stable interface protective film to inhibit the reduction of lithium consumption of PTFE.

Benefits of technology

It improves the first discharge capacity (first effect) and cycle life of the battery, and extends the battery life time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a secondary battery and an electric device. The secondary battery comprises a positive pole piece, a negative pole piece and an electrolyte, the negative pole piece comprises a negative active layer, the negative active layer comprises a binder, and the binder comprises polytetrafluoroethylene; based on the mass of the negative electrode active layer, the mass content of polytetrafluoroethylene is a; in the negative electrode active layer, part or all of the polytetrafluoroethylene exists in a fibration form, and the fiber amount of the polytetrafluoroethylene is b; the electrolyte comprises a solvent and an additive, the solvent comprises carbonic ester and carboxylic ester, and the additive comprises lithium borate; based on the mass of the electrolyte, the mass content of the lithium borate salt additive is c; wherein c is more than or equal to 0.005 * a * b and less than or equal to 0.02 * a * b. According to the secondary battery disclosed by the invention, the electrolyte is reduced on the surface of the negative pole piece early to form a stable interface protection film, so that the negative active material can be passivated well while the reduction lithium consumption of the negative binder is inhibited, and the first effect and circulation of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] The dry electrode process is a comprehensive upgrade over the traditional wet process, which can bring about a huge improvement in battery performance and cost. In terms of battery performance, dry-process batteries can achieve higher energy density, and the battery's electrical performance and safety performance are both better; in the manufacturing process, dry electrodes have fewer steps, lower manufacturing costs and energy consumption, and the raw materials are environmentally friendly, more suitable for large-scale production, and can bring greater economic benefits. On the application side, dry-process batteries are more suitable for the manufacturing needs of new-generation batteries such as solid-state batteries and large cylindrical batteries.

[0003] However, the current domestic dry electrode technology is not yet fully mature, and there are still many process technical difficulties. The performance of batteries in the dry process system needs to be further improved. Summary of the invention

[0004] The inventors of this application found that, on the one hand, the introduction of the dry process will make the active area of ​​the active material (graphite or silicon) larger, and it is easier to induce side reactions involving lithium ions, especially during the first charge and discharge process, the irreversible lithium consumption is large; on the other hand, the specific surface area of ​​the binder polytetrafluoroethylene (PTFE) unique to the dry process increases a lot after fiberization, and there will be a significant reduction phenomenon of lithium capacity consumption, which makes the first discharge capacity (first efficiency) of the dry electrode lithium ion battery low, and it will cause faster capacity decay in the early stage of the cycle, and PTFE is not resistant to reduction, and it will obviously consume lithium ions in the first charge and discharge overcharge. These characteristics make the first efficiency of the dry process system battery low, and the capacity decay is faster during the cycle. In response to this discovery, this application uses a special electrolyte additive lithium borate salt, which is preferentially reduced during the first charge and discharge process due to its high reduction potential (vs Li), and will form an effective passivation film on the surface of the active material and the binder, thereby inhibiting the capacity loss caused by the reduction of the binder PTFE, improving the first efficiency of the battery, and extending the cycle life of the battery.

[0005] The first aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode active layer, wherein the negative electrode active layer includes a negative electrode active material and a binder, wherein the binder includes polytetrafluoroethylene; based on the mass of the negative electrode active layer, the mass content of the polytetrafluoroethylene is a; in the negative electrode active layer, the polytetrafluoroethylene is partially or completely present in a fibrous form, and the fiber amount of the polytetrafluoroethylene is b, wherein the fiber amount is based on an observation area of ​​350 μm in 9 different regions scanned and photographed under a scanning electron microscope (SEM) at a magnification of 5000 times. 2The statistical average of the number of fibers in the electrode surface morphology diagram; the electrolyte comprises a solvent and an additive, the solvent comprises a carbonate and a carboxylate, and the additive comprises a lithium borate salt; based on the mass of the electrolyte, the mass content of the lithium borate salt additive is c; wherein 0.005×a×b≤ c ≤0.02×a×b.

[0006] A second aspect of the present application provides an electrical device, wherein the electrical device comprises the secondary battery described in the first aspect.

[0007] The beneficial effects of this application are: The secondary battery of the present application reduces the electrolyte on the surface of the dry negative electrode plate early to form a stable interface protection film, which inhibits the reduction and lithium consumption of the negative electrode binder and can better passivate the negative electrode active material, thereby improving the initial efficiency and cycle life of the secondary battery. DETAILED DESCRIPTION

[0008] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.

[0009] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0010] A list of items connected by the terms "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.

[0011] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0012] Primary and secondary batteries The secondary battery provided by the present application includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode active layer, wherein the negative electrode active layer includes a negative electrode active material and a binder, wherein the binder includes polytetrafluoroethylene; based on the mass of the negative electrode active layer, the mass content of the polytetrafluoroethylene is a; in the negative electrode active layer, the polytetrafluoroethylene is partially or completely present in a fibrous form, and the fiber amount of the polytetrafluoroethylene is b, and the fiber amount is based on an observation area of ​​350 μm in 9 different regions scanned and photographed by SEM at a magnification of 5000 times 2 The statistical average of the number of fibers in the electrode surface morphology diagram; the electrolyte comprises a solvent and an additive, the solvent comprises a carbonate and a carboxylate, and the additive comprises a lithium borate salt; based on the mass of the electrolyte, the mass content of the lithium borate salt additive is c; wherein 0.005×a×b≤ c ≤0.02×a×b.

[0013] The inventors of the present application have found that the use of PTFE as a binder in the negative electrode sheet will significantly reduce the first effect of the battery, which is related to the poor reduction stability and irreversible decomposition of PTFE. However, by utilizing the high reduction potential of borates to preferentially reduce PTFE during the first charge and discharge process, the reduction and lithium consumption of PTFE can be suppressed, and an effective passivation film can also be formed on the surface of the active material and PTFE fiber, reducing the undesirable side reactions that occur when the electrolyte contacts the active material and PTFE, thereby improving the first effect and cycle of the secondary battery. The present invention effectively improves the first effect and cycle of the secondary battery by selecting an appropriate amount of lithium borate salt additive according to the PTFE content and the fiber amount.

[0014] In some embodiments, the negative electrode active layer does not contain a solvent, specifically does not contain detectable processing solvents, processing solvent residues and processing solvent impurities. These processing solvents include but are not limited to water, pyrrolidone, acetate, ketone, alcohol, glycol, toluene, xylene.

[0015] In some embodiments, c is illustratively 0.005×a×b, 0.008×a×b, 0.01×a×b, 0.012×a×b, 0.015×a×b, 0.018×a×b, 0.02×a×b or any value therebetween. In some preferred embodiments, 0.01×a×b≤ c ≤0.015×a×b.

[0016] In some embodiments, a is illustratively 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or any value therebetween. In some preferred embodiments, 0.5%≤a≤3%.

[0017] In some embodiments, b is illustratively 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50, 52, 55, 58, 60, 62, 65, 68, 70, 72, 75, 78, 80 or any value therebetween. In some preferred embodiments, 50≤b≤70.

[0018] In some embodiments, c is illustratively 0.1%, 0.3%, 0.5%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any value therebetween. In some preferred embodiments, 0.5%≤c≤2%. In some preferred embodiments, 1% <c<2%。

[0019] In some embodiments, the lithium borate salt is selected from at least one of lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium tetrafluoroborate. In some preferred embodiments, the lithium borate salt is lithium bis(oxalatoborate) or lithium difluorooxalatoborate.

[0020] In some embodiments, the carboxylate comprises a chain carboxylate, and the chain carboxylate is selected from at least one of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorocarboxylate. In some embodiments, the carboxylate is methyl acetate. In some embodiments, based on the mass of the solvent, the mass content of the carboxylate is 5%-15%, exemplarily 5%, 8%, 10%, 12%, 15% or any value therebetween.

[0021] In some embodiments, the carbonate includes linear carbonate and cyclic carbonate. In some embodiments, the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate. In some embodiments, the cyclic carbonate includes non-fluorinated cyclic carbonate and fluorinated cyclic carbonate, and the non-fluorinated cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate, and butylene carbonate, and the fluorinated cyclic carbonate includes fluorinated ethylene carbonate. In some embodiments, the linear carbonate includes dimethyl carbonate and ethyl methyl carbonate, and the non-fluorinated cyclic carbonate includes ethylene carbonate, and the fluorinated cyclic carbonate includes fluorinated ethylene carbonate.

[0022] In some embodiments, based on the quality of the solvent, the mass content of the linear carbonate is 40%-70%, exemplified by 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70% or any value therebetween. In some embodiments, based on the quality of the solvent, the mass content of the fluorinated cyclic carbonate is 5%-15%, exemplified by 5%, 8%, 10%, 12%, 15% or any value therebetween. In some embodiments, based on the quality of the solvent, the mass content of the non-fluorinated cyclic carbonate is 1%-15%, exemplified by 1%, 3%, 5%, 8%, 10%, 12%, 15% or any value therebetween.

[0023] Increasing the ratio of chain carbonate and chain carboxylic acid ester in the electrolyte solvent is beneficial to reducing the viscosity of the electrolyte, improving the wettability of the electrolyte, and helping to further improve the initial efficiency and cycle of the secondary battery.

[0024] In some embodiments, the electrolyte further comprises other additives, and the other additives are selected from at least one of vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene disulfonate, lithium difluorophosphate, succinonitrile, adiponitrile and 1,3,6 hexane trinitrile. In some embodiments, based on the mass of the electrolyte, the mass content of the other additives is 0.1%-15%. In some embodiments, the other additives include vinylene carbonate and lithium difluorophosphate, and based on the mass of the electrolyte, the mass content of the vinylene carbonate is 0.01%-5%, and the mass content of the lithium difluorophosphate is 0.01%-2%.

[0025] In some embodiments, the electrolyte further comprises a lithium salt, and the lithium salt comprises lithium hexafluorophosphate and / or lithium bis(trifluoromethanesulfonyl)imide. In some embodiments, the lithium salt comprises lithium hexafluorophosphate.

[0026] In some embodiments, the solvent includes 5%-15% methyl acetate, 1%-15% cyclic ethylene carbonate and / or cyclic propylene carbonate, 40%-70% dimethyl carbonate and / or ethyl methyl carbonate, and 5%-15% fluoroethylene carbonate, based on the mass of the solvent.

[0027] In some embodiments, based on the mass of the electrolyte, the additive includes 0.3%-3% of lithium borate salt, 0.01%-5% of vinylene carbonate, and 0.01%-2% of lithium difluorophosphate.

[0028] In some embodiments, the negative electrode plate is a dry-process negative electrode plate, which can be prepared by a conventional dry process in the art.

[0029] In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material, the carbon-based material includes at least one of artificial graphite and natural graphite, and the silicon-based material includes at least one of a silicon oxide compound and a silicon-carbon composite. In some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material is 5%-30%, exemplarily 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any value therebetween. In some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material is 8%-15%. As we all know, silicon negative electrodes have always faced the problem of low first efficiency. The higher the silicon content in the negative electrode active material, the more prominent the first efficiency problem. The introduction of the dry process will lead to an increase in the active area of ​​the silicon negative electrode active material, making it easier to increase the consumption of irreversible lithium during the first charge and discharge process, further reducing the first efficiency. However, the electrolyte additive of the present invention can be preferentially reduced during the first charge and discharge process due to its high reduction potential to form a stable interface film, which can effectively improve the first efficiency and cycle performance of the dry-process graphite-doped silicon negative electrode battery.

[0030] In some embodiments, the negative electrode plate further includes a second binder, and the second binder is selected from one or more of polyvinylidene fluoride, styrene-butadiene rubber, nitrile rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and sodium alginate. In some embodiments, the mass ratio of polytetrafluoroethylene to the second binder is (0.5-5):1. In some embodiments, the negative electrode plate further includes a conductive agent, and the conductive agent is selected from one or more of conductive carbon black, carbon fiber, graphene, conductive graphite, and carbon nanotubes.

[0031] In some embodiments, based on the mass of the negative electrode active layer, the negative electrode plate includes 70%-90% of carbon-based active material, 5%-30% of silicon-based active material, 0.5%-3% of PTFE, 0.2%-1.5% of the second binder, and 0.5%-5% of the conductive agent.

[0032] In some embodiments, the negative electrode plate is made by a method comprising the following steps: (I) mixing the negative electrode active material and the conductive agent to obtain a mixture A; (II) mixing the mixture A with the polytetrafluoroethylene and performing a fiberization treatment to obtain a mixture B; (III) rolling the mixture B into a film to form a self-supporting film; (IV) Compounding the self-supporting film with a current collector to obtain the negative electrode sheet.

[0033] In some embodiments, the negative electrode active layer further includes the second binder, and the negative electrode plate is prepared by a method comprising the following steps: (I) dry-mixing the negative electrode active material, the second binder and the conductive agent to obtain a mixture A; (II) dry-mixing the mixture A with the polytetrafluoroethylene and performing a fiberization treatment to obtain a mixture B; (III) rolling the mixture B into a film to form a self-supporting film; (IV) Compounding the self-supporting film with a current collector to obtain the negative electrode sheet.

[0034] In some embodiments, in step (I) and step (II), the mixing line speed is 15m / s-40m / s, and the mixing temperature is 20°C-80°C. In some embodiments, in step (III), the roller surface temperature of the rolling is 70°C-150°C, such as 90°C-130°C, and the roller line pressure of the rolling is 0.01t / cm-2t / cm. In some embodiments, in step (IV), the compounding temperature is 100°C-150°C, and the compounding roller line pressure is 0.01t / cm-0.5t / cm.

[0035] In some embodiments, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium-rich manganese-based materials.

[0036] In some embodiments, the positive electrode active material includes a LiNi m Co n A (1-m-n) O 2 The lithium nickel transition metal oxide shown, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1. Wherein, m is exemplarily 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any value therebetween, and n is exemplarily 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any value therebetween. In some embodiments, 0.7≤m≤1, 0≤n≤0.3.

[0037] In some embodiments, the positive electrode sheet further comprises a binder and a conductive material. In some embodiments, the positive electrode sheet is a wet positive electrode sheet, which is prepared by a conventional wet process. In some embodiments, the positive electrode sheet is a dry positive electrode sheet, which is prepared by a dry process.

[0038] In some embodiments, the secondary battery comprises a positive electrode sheet, a dry negative electrode sheet, and an electrolyte. In some embodiments, the secondary battery comprises a wet positive electrode sheet, a dry negative electrode sheet, and an electrolyte. In some embodiments, the secondary battery comprises a dry positive electrode sheet, a dry negative electrode sheet, and an electrolyte.

[0039] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; or a soft package, such as a bag-type soft package, and the material of the soft package is non-limitingly polypropylene, polybutylene terephthalate, and polybutylene succinate. In the present application, there is no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0040] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0041] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0042] 2. Device The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module or battery pack.

[0043] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.

[0044] In other embodiments, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source. Examples and Comparative Examples

[0045] In this application, unless otherwise specified, all materials or reagents used are commercially available. Example 1

[0046] Preparation of the electrolyte: In a nitrogen-protected glove box (water content <1ppm, oxygen content <1ppm), 10wt% of ethylene carbonate, 45.5wt% of dimethyl carbonate, 9wt% of ethyl methyl carbonate, 11wt% of methyl acetate, 10wt% of fluoroethylene carbonate, 0.5wt% of vinylene carbonate, 1% of lithium difluorophosphate and 13wt% of lithium hexafluorophosphate were mixed to prepare a basic electrolyte, and then 0.41wt% of lithium borate was added to the basic electrolyte and stirred to obtain the electrolyte of Example 1.

[0047] Preparation of negative electrode sheet: Active material (graphite and silicon-carbon composite weight ratio 90:10) and conductive agent carbon black are mixed in a weight ratio of 96:1.5, and mechanically stirred for 3~5min to obtain mixture M1; a second binder sodium carboxymethyl cellulose (CMC-Na) particles are added to the mixture M1, and mechanically stirred for 3~5min to obtain a mixture M2, wherein the weight ratio of the second binder to the conductive agent is 0.5:1.5; a first binder polytetrafluoroethylene (PTFE) is added to the mixture M2, and mechanically stirred for 3~5min to obtain a fiberized mixture, wherein the weight ratio of the first binder to the conductive agent is 2:1.5. Each mechanical stirring is mixed by high-speed shearing, the shear speed limit is controlled at 40m / s, and the shear temperature is controlled at 20℃-80℃. The fiberized mixture is rolled into a film on a roller machine, the roller surface temperature is set to 110℃, and the roller line pressure is set to 0.4t / cm to form a negative electrode self-supporting film. The obtained self-supporting film was compounded with the current collector, the roller surface temperature was set to 120° C., and the line pressure between the rollers was set to 0.08 t / cm to prepare a negative electrode sheet.

[0048] Preparation of positive electrode: Mix the binder polyvinylidene fluoride (PVDF) with water, stir to obtain glue, and then add the active material LiNi 0.8 Co 0.1 Mn 0.1 O 2 and conductive agent carbon black are added to the glue, mixed and stirred to obtain positive electrode slurry, wherein the weight ratio of active material, binder and conductive agent is 96:1.5:2.5; the positive electrode slurry is evenly coated on aluminum foil, and after baking, rolling and slitting, the positive electrode sheet is obtained.

[0049] Diaphragm: Polyethylene ceramic coated composite diaphragm is selected.

[0050] Preparation of lithium-ion battery: stack the prepared positive electrode sheet, separator, and negative electrode sheet in order, place the separator between the positive and negative electrode sheets, and wind them to obtain a bare cell; place the bare cell in an aluminum-plastic film outer package, inject the prepared electrolyte after sufficient drying, wherein the electrolyte injection amount is 8.2g, and then obtain a lithium-ion battery after formation, degassing, and secondary sealing. Example 2-11 and Comparative Example 1-2

[0051] Examples 2 to 11 and Comparative Examples 1 to 2 are achieved by adjusting the film forming temperature, the type and content of the electrolyte lithium borate salt additive, the content of the first binder PTFE, and the amount of PTFE fiber in the pole piece on the basis of Example 1. The specific adjustment measures and detailed data are shown in Table 1. The sum of the mass content of PTFE and the active material in each example and comparative example is 98%, and the content of the second binder and the conductive agent are the same.

[0052] Table 1 Test Method

[0053] 1. Fiber quantity The negative electrode sheets of each embodiment and comparative example were cut into samples with a size of 0.6 cm × 0.6 cm, sprayed with gold, and then placed on a sample stage. The surface morphology of the samples was photographed using a Zeiss scanning electron microscope. Three parallel samples were taken from each electrode sheet, and three different sites of each parallel sample were taken for SEM photography. The magnification was 5000 times (i.e., the SEM scale was 2 μm), and the area of ​​each area photographed and observed was 350 μm 2 , the regional photos of 9 different sites of 3 parallel samples of each pole piece are coded as 1-1, 1-2, 1-3, 2-1, 2-2, 2-3, 3-1, 3-2, 3-3. A machine learning model is established to count the fiber amount in each SEM photo, and the average value is the fiber amount of the pole piece. Taking Example 3 as an example, the test record and mean of the fiber amount are as follows: Table 2

[0054] 2. First-time test During the test, the lithium-ion battery was first charged to 4.2V at 0.1C constant current and constant voltage at 25°C, left to stand for 5 minutes, and then discharged to 2.5V at 0.1C constant current and left to stand for 5 minutes. The battery's first coulombic efficiency (first efficiency) = first discharge capacity / first charge specific capacity) × 100%.

[0055] 3. Cycle test In a 45°C environment, charge the lithium-ion battery to 4.2V at 1C constant current and constant voltage, let it rest for 5 minutes, then discharge it to 2.5V at 1C constant current, let it rest for 30 minutes, and repeat the charge and discharge process until the battery's capacity retention rate decays to 80%, and record the number of battery cycles. Test Results

[0056] Table 3

[0057] By comparing the embodiments and comparative examples, it can be found that when there is no lithium borate salt additive, the first efficiency and cycle of the secondary battery are lower. This is because the fiberized PTFE has a larger specific surface area and will undergo a reduction reaction, continuously consuming lithium ions during the first and subsequent charge and discharge processes, resulting in reduced first efficiency and cycle of the battery.

[0058] By comparing Comparative Examples 1 and 2, it can be found that when the PTFE content is lower, the amount of fiberization is also lower. Although the initial efficiency will be appropriately improved, the cycle decay is faster. This is because the insufficient amount of fiberization makes the adhesion between the main material particles worse during the charge and discharge process, and the pole piece expands, resulting in the interruption of the lithium ion transmission path and causing capacity loss.

[0059] From Examples 1-4, it can be found that as the PTFE content increases, the amount of fiberization will also increase. At the same time, by adjusting the content of the additive lithium dioxalate borate, the first effect and cycle of the battery will also improve. This is because PTFE forms a sufficient number of fibers in the diaphragm, the main material particles are in good contact, and the cycle performance will also improve. At the same time, the increase in the content of additives will also passivate PTFE in advance, reduce its consumption of lithium capacity by reduction, and thus improve the first effect. However, when the PTFE content is large, as the amount of fiberization continues to increase, the increase in additives is not enough to fully passivate the effect of its reduction on the first effect, and the first effect will be reduced (Example 4). At the same time, since the binder itself is not conductive, when its content is high, it will increase the impedance of the diaphragm, thereby increasing the reversible capacity loss, and ultimately leading to a reduction in cycle life.

[0060] By comparing Examples 3, 5-6 and the comparative example, it can be found that the three lithium borate salt additives all significantly improve the first effect and the cycle, among which lithium dioxalate borate has the best effect. This is related to the film characteristics formed after the reduction of different additives. The film formed after the reduction of lithium dioxalate borate has better stability and therefore significantly improves the first effect and the cycle.

[0061] In Example 7, when the two additives are used at the same time, the cycle and the first effect are not improved. This is because during the first charge and discharge process, the consumption of the additive at a certain potential will continue to enter a lower (or higher) potential as the content increases to a certain extent. The reduction potentials of lithium dioxalatoborate and lithium difluorooxalatoborate are similar (2.2V vs Li). When the two are used at the same time, the total content is large, and they will continue to be consumed at the corresponding reduction potential, and the first effect will be reduced. At the same time, the high content brings higher impedance, causing the loss of reversible capacity and reducing the cycle.

[0062] By comparing Examples 3, 8-10, it can be found that the higher the film forming temperature, the more fibers there are. This is because high temperature accelerates the molecular thermal motion, and the possibility of PTFE slipping along the C axis is greater, so the number of fibers is greater. At the same time, the content of the additive is adjusted, and the first effect and cycle are also improved. However, when the temperature is higher (120°C), the first effect and cycle will decrease. This is because higher temperature will bring more fibers, but more fibers will increase impedance, bring more polarization capacity loss, and lead to a decrease in the first effect and cycle.

[0063] By comparing Examples 3 and 11, it can be found that low film-forming temperature and high PTFE content can also bring more fibers, and the first effect and circulation can also reach similar levels. However, considering the cost of PTFE, Example 3 is better.

[0064] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the scope of the present application as described in the appended claims.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode plate includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material and a binder, the binder includes polytetrafluoroethylene; based on the mass of the negative electrode active layer, the mass content of the polytetrafluoroethylene is a; in the negative electrode active layer, the polytetrafluoroethylene is partially or completely in the form of fibers, the amount of the polytetrafluoroethylene fibers is b, and the amount of fibers is based on an observation area of ​​350 μm in 9 different areas scanned and photographed by SEM at a magnification of 5000 times 2 The statistical average of the number of fibers in the electrode surface topography; The electrolyte comprises a solvent and an additive, wherein the solvent comprises a carbonate ester and a carboxylate ester, and the additive comprises a lithium borate salt; based on the mass of the electrolyte, the mass content of the lithium borate salt additive is c; Among them, 0.005×a×b≤ c ≤0.02×a×b.

2. The secondary battery according to claim 1, characterized in that 0.01×a×b≤c ≤0.015×a×b.

3. The secondary battery according to claim 1 or 2, characterized in that: The secondary battery satisfies at least one of the following conditions: (i) 0 <a≤5%; (ii) 20 <b≤80; (iii) 0 <c≤3%。 4. The secondary battery according to claim 1 or 2, characterized in that: The secondary battery satisfies at least one of the following conditions: (iv) 0.5%≤a≤3%; (v) 50 ≤ b ≤ 70; (vi) 0.5% ≤ c ≤ 2%.

5. The secondary battery according to claim 1 or 2, characterized in that: The lithium borate salt is selected from at least one of lithium dioxalate borate, lithium difluorooxalate borate and lithium tetrafluoroborate.

6. The secondary battery according to claim 5, characterized in that: The lithium borate salt is lithium dioxalate borate or lithium difluorooxalate borate.

7. The secondary battery according to claim 1 or 2, characterized in that: The secondary battery satisfies at least one of the following conditions: (a) the carboxylic acid ester is at least one selected from methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorocarboxylic acid ester; (b) the carbonate comprises a linear carbonate and a cyclic carbonate, the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate, the cyclic carbonate comprises a non-fluorinated cyclic carbonate and a fluorinated cyclic carbonate, the non-fluorinated cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate and butylene carbonate, and the fluorinated cyclic carbonate comprises fluorinated ethylene carbonate; (c) the additive further comprises at least one selected from vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene methane disulfonate, lithium difluoro oxalato borate, lithium dioxalato borate, lithium difluorophosphate, succinonitrile, adiponitrile and 1,3,6-hexane trinitrile; (d) the negative electrode active material comprises a carbon-based material and a silicon-based material, the carbon-based material comprises graphite, and the silicon-based material comprises at least one of a silicon-oxygen compound and a silicon-carbon composite; (e) The positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a LiNi m Co n A (1-m-n) The lithium nickel transition metal oxide shown in O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1.

8. The secondary battery according to claim 7, characterized in that: (a) based on the mass of the solvent, the mass content of the carboxylic acid ester is 5%-15%; (b) based on the mass of the solvent, the mass content of the linear carbonate is 40%-70%, the mass content of the fluorinated cyclic carbonate is 5%-15%, and the mass content of the non-fluorinated cyclic carbonate is 1%-15%; (c) the additive comprises vinylene carbonate and lithium difluorophosphate; (d) based on the mass of the negative electrode active material, the mass content of the silicon-based material is 5%-30%; (e) In the chemical formula of the lithium nickel transition metal oxide, 0.7≤m≤1, 0≤n≤0.

3.

9. The secondary battery according to claim 1 or 2, characterized in that: The negative electrode plate is prepared by a method comprising the following steps: (I) mixing the negative electrode active material and the conductive agent to obtain a mixture A; (II) mixing the mixture A with the polytetrafluoroethylene and performing a fiberization treatment to obtain a mixture B; (III) rolling the mixture B into a film to form a self-supporting film; (IV) Compounding the self-supporting film with a current collector to obtain the negative electrode sheet.

10. An electrical device comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Secondary battery and device

    CN116314595A

  • Secondary battery and device

    CN116470143A

  • Electrolyte additive for forming solid electrolyte interface on polytetrafluoroethylene-containing negative electrode and battery comprising same

    CN119208728A

  • Semiconductor package

    KR1020240030106A

  • Lithium secondary battery with improved elecrochemical property by dry process and electrolyte additive content control and manufacturing method thereof

    KR102636223B1